ASSISTANCE PROGRAM FOR THE COMPOSITION OF SCHOLARLY ARTICLES BY TEACHERS AT MIS DDI LAPEO - Fatimah, Meryta Febrilian; Qadrini, Laila; Rachman, Hirman (Universitas Pahlawan Tuanku Tambusai, 2023)
An academic article is acknowledged as a scholarly endeavour, encapsulating the research findings of academicians. These articles are conventionally disseminated through academic journals. In compliance with governmental directives, educators are required to draft and publish scholarly articles in such journals. To facilitate adherence to this mandate, the provision of training in academic article writing is imperative. This training aims to scrutinize and reconcile articles previously authored by educators with prevailing scholarly writing standards. The participants of this program were educators from MIS DDI Lapeo, with the goal of augmenting their proficiency in the composition of academic articles. This program saw the participation of 14 educators from MIS DDI Lapeo, encompassing both classical and individualized methodologies. The classical methodology entailed a structured training process in academic article preparation, commencing with an exposition on journals, articles, and the core principles of article creation, culminating in the actual drafting of academic articles. Conversely, the individualized approach was implemented in the context of one-on-one mentorship for article composition. The outcomes of this mentorship included an enhanced understanding among educators in the formulation of academic articles and an increased propensity towards engaging in article writing. Notable challenges encountered by these educators in the process of scholarly writing encompassed a paucity of references, constrained time allocations, and a lack of creative ingenuity, predominantly manifesting in their focus on Classroom Action Research.